Reavaliação de critérios estruturais na hidrogeologia de terrenos cristalinos, com ênfase na neotectônica e sensoriamento remoto - Coriolano, Ana Catarina Fernandes (2002)
Hydrogeological prospecting in Northeast Brazil and in other crystalline terrains has been developed on the basis of structural and regional geology concepts that date back to the 50-60 decades and, as such, demand a natural re-evaluation and update. In this kind of terrain, the percolation and accumulation of ground water are controlled by fractures and other types of discontinuities, such as foliations and geological contacts that, through weathering, impart porosity and permeability to the rocks, allowing water flow and storage. Several factors should be considered in the process of locating water wells, as discussed in the literature. Among these, the kind of structures, fracture geometry (including aperture and connectivity) and their geological and chronological context. It is important to correlate fracture systems with the regional neotectonic framework. Fractures at low angle (sub parallel) with the principal stress axis (s1) are those which tend to open (actually they work as tension joints) and, in principle, would present major hydric potential; in the opposite side, fractures at high angle to s1 would behave as closed by a compressional component. Fractures diagonal to the compression and tension axes correspond to shear fractures and, due to their connectivity with second fractures, are also important in terms of hydric potential. Uplift followed by terrain denudation leads to decompression and a general tendency to open (aided by weathering processes) fractures and other rock discontinuities, at different orientations. Low angle fractures, formed in this context, are equally important to increase connectivity, collection of water and recharge of the aquifer systems. In a general way, an opening component (neotectonic or by terrain decompression) and several models to increase fracture connectivity correlate with a greater hydric potential of these structures. Together with parallel research, this thesis addresses models of ground water occurrence in crystalline terrains, either improving well established concepts like the (Riacho-Fenda model), but also stressing other possibilities, like the role of alluvium and paleo-regoliths (the Calha Elúvio-Aluvionar model) and of strongly altered, permo-porous zones placed at variable depths below the present surface, flanking several types of discontinuities, especially interconnected fracture arrays (the Bolsões de Intemperismo model). Different methodological approaches are also discussed in order to improve success rates in the location of water wells in crystalline terrains. In this methodological review, a number of case studies were selected in the eastern domain of the State of Rio Grande do Norte, involving the localities of Santa Cruz, Santo Antônio, Serrinha, Nova Cruz, Montanhas, Lagoa de Pedras and Lagoa Salgada. Besides the neotectonic analysis of brittle structures, this Thesis addresses the validation of remote sensing as a tool for ground water prospecting. Several techniques were tested in order to detect and select areas with higher potential for ground water accumulation, using Landsat 5-TM and RADARSAT images, besides conventional aerial photos. A number of filters were tested to emphasize lineaments in the images, improving their discrimination, to identify areas with higher overburden humidity, which could reflect subsurface water accumulation, as well as alluvium and other sedimentary covers that might act as recharge zones. The work started with a regional analysis with the orbital images, followed by analysis of aerial photos, up to a detailed structural study of rock exposures in the terrain. This last step involved the analysis of outcrops surrounding wells (in a ray of approximately 10 to 100 m) with distinct productivities, including dry examples. At the level required for detail, it was not possible to accomplish a statistical approach using the available well data catalogs, which lack the desired specific information. The methodology worked out in this Thesis must undergo a testing phase through location of new water wells. An increase in the success rates as desired will led to a further consolidation step with wider divulgation of the methodology to private companies and governmental agencies involved in ground water prospecting in crystalline terrains